Profile Of Pleural Fluid Adenosine Deaminase And Protein Levels In Tuberculous Pleural Effusion At Adam Malik Hospital Indonesia - Marisi Ester Nova Sihite; Syamsul Bihar (Jurnal Impresi Indonesia, 2025)
Tuberculosis remains one of the most prevalent infectious diseases worldwide. In addition to affecting the lungs, Mycobacterium tuberculosis infection can also cause extrapulmonary tuberculosis, including pleural effusion. Tuberculous pleural effusion is a relatively common condition, with an incidence ranging from three to thirty percent of total tuberculosis cases. Diagnosing tuberculous pleural effusion presents a clinical challenge due to nonspecific symptoms and limitations of conventional diagnostic methods. Biomarker testing, such as measuring Adenosine Deaminase levels in pleural fluid, has been widely used as a diagnostic method due to its high sensitivity and specificity in distinguishing tuberculous pleural effusion from other causes. Method: This study aims to analyze Adenosine Deaminase levels and pleural fluid protein levels in patients with pleural effusion. A descriptive study with a cross-sectional approach was conducted on thirty-five samples that met the inclusion criteria. Result: The results showed that the mean Adenosine Deaminase level was sixty-one point nine seven grams per liter, with a standard deviation of fifty-eight point three one four and a median value of forty-one grams per liter. The mean pleural fluid protein level was four point five grams per deciliter, with a standard deviation of one point five six and a median value of four point three one grams per deciliter. Conclusion: The analysis revealed significant differences in Adenosine Deaminase and pleural fluid protein levels based on nutritional status, comorbid diseases, and bacteriological examination results. Furthermore, a positive and significant correlation was found between Adenosine Deaminase and pleural fluid protein levels, where an increase in Adenosine Deaminase levels was associated with higher pleural fluid protein levels. Clinical factors such as nutritional status, comorbid diseases, and bacteriological examination results play a role in determining the levels of these biomarkers.